Diagnosing erectile dysfunction could save your patient’s life - Brock, Gerald (Canadian Urological Association Journal, 2014)
Erectile dysfunction and coronary artery disease are increasingly recognized as different clinical manifestations of the same process. Because the smaller vessels of the penis may be affected by plaque burden much earlier than the larger coronary, internal carotid, and femoral arteries, men may present with symptoms of erectile dysfunction long before signs of cardiovascular disease manifest. This presents an opportunity for the urologist to not only treat the sexual dysfunction and uncover occult coronary disease, but also screen for cardiac risk, as even men with mild arteriogenic erectile dysfunction may be at risk for cardiovascular disease.